دور تقنية التحسين المستمر في تخفيض التكاليف (دراسة تطبيقية في معمل آسو لإنتاج الطابوق الأحمر) - نجم, بصيرة مجيد; عطاء, ئاويز محمد (Sulaimani Journal for Humanities, 2022)
The research aims to shed light on the most important tools of modern management accounting, which is the continuous improvement technique that focuses on reducing costs through the application of continuous improvement methods represented in continuous improvement costs, target cost and benchmarking in the Aso factory for the production of red bricks to reach the rationalization of the cost of the product and maintain the required quality and improve company profitability. To achieve the objectives of the research and then use the data of the Aso laboratory to produce red bricks for the years 2018 and 2019. The research reached several results, the most important of which was that the research sample laboratory does not apply methods of continuous improvement with its scientific concepts and that if the laboratory adopts the research sample for these methods, such as reducing costs by an amount (18,059,290,404) and (14,391,726,946) for the years 2018 and 2019, respectively. After reducing costs, one of the success factors for the plant in light of intense competition, and producing bricks at low costs is one of the strategies that the plant competes with to improve profits. The results of the research show that the use and success of the targeted costing methods, the cost of continuous improvement and benchmarking in the lab needs the support of senior management, as it is this administration that sets these methods as a strategy for it, and the responsibility for use is not limited to senior management, as to other administrative levels such as middle management, supervisors and workers A major role in the success of its application, and the factory adopted the traditional price policy in pricing on the basis of competitors' prices set without considering the costs of the brick product, which created a wide cost gap between the selling price, cost and profit. The research also reached several recommendations, the most important of which was that the laboratory should pay attention to adopting the method of Continuous improvement to improve production processes because it has a significant and prominent role in enhancing the competitive capabilities of the laboratory in the face of the rapidly changing external environment and what is reflected in achieving the goals of the laboratory in survival, growth and continuing to provide products with high quality. Low prices and high quality, and the need to adopt continuous improvement methods and other accompanying techniques, will contribute to increasing the share of the plant in the local market and improving its competitive position by strengthening its competitive position and reducing the costs of its product and at the same time maintaining the required quality to ensure meeting the needs of customers and the need for management attention lab application Continuous improvement methods (target cost - benchmark comparison - continuous improvement cost) because it contributes to reducing costs and increasing competitiveness in the market Keywords: continuous improve
Keywords: continuous improvement; Target cost; Kaizen cost; Benchmarking; Reduce costs